Keadilan Menang: Melindungi Korban Main Hakim Sendiri (Eigenrechting) - Adiyatma, Septhian Eka (Ius Poenale, 2023)
The rise of vigilantism in Indonesia, marked by public violence against alleged criminals that sometimes results in fatalities, reflects a significant misunderstanding of justice and a lack of specific legislation on vigilante actions. This behavior, akin to torture under Indonesian law, is fueled by public distrust in law enforcement. Research employing both the historical and current Criminal Codes, alongside a sociological analysis, highlights the government's crucial role in legally shaping societal behavior. Discussions on vigilantism involve examining its nature, the legal protections and assistance available, and shaping a societal view that considers both perpetrators and victims. These conversations aim to uphold human rights within the Pancasila ideology, striving for public order and justice that require collective understanding and effort. Addressing vigilantism effectively necessitates both preventive measures to discourage such actions and repressive responses to penalize offenders, ensuring that societal actions align with justice and human rights objectives.